Using CRF Tool for Analyzing the Resilience of Cities - S. M. Al-Jawari; N. AbdulRazak Hasach Albasri; O. Jassim Al-Mosherefawi (Civil Engineering Journal, 2022)
The new sustainable development goals set by the UN include a goal of making cities inclusive, safe, sustainable, and resilient. Cities are growing at huge rates, and conditions of deteriorating QOL̛s are increasing in the form of poor access to services, and slums are remarkable, especially in the cities of the Middle East; hence, the research problem can arise from a lack of knowledge regarding the in determination of a way to assess the resilience of cities to develop mechanisms that will improve the quality of urban life. In this study, a tool called CRF has been applied for the assessment of the city's resilience principles of health and quality of life, economics and social, infrastructure and environmental systems, and the principles of governance and strategic leadership. The research aims to determine the efficiency of Kufa City in achieving the principles of resilience according to the CRF. The research is based on the descriptive analytical method. The research concluded that the city of Kufa achieves low levels of some indicators of resilience, especially on the imposition of security and the rule of law, transportation, and communications, and achieves reasonable rates of resilience regarding opportunities for creating a sustainable economy and achieving basic needs. Doi: 10.28991/CEJ-2022-08-10-013 Full Text: PDF